Toward Easy and Rapid Bronchial Occlusion With an Endobronchial Watanabe Spigot: A New Technique Using a Guide Sheath and Curette. Issue 2 (April 2020) - Mizumori, Yasuyuki; Nakahara, Yasuharu; Hirata, Nobuya; Hiraoka, Ryota; Kominami, Ryota; Hirano, Katsuya; Hanaoka, Kenji; Katsuda, Rinko; Miyake, Kohei; Kawamura, Tetsuji
Abstract : Background: Bronchial occlusion using an endobronchial Watanabe spigot (EWS) is reportedly effective for intractable bronchopleural fistula. Here, we describe a rapid and easy method for bronchial occlusion using a guide sheath (GS) and curette. Methods: Thirty consecutive patients who underwent bronchial occlusion under mild sedation between October 2014 and February 2018 were enrolled. The devices used were a flexible bronchoscope (BF-1T260 or BF-1TQ290), GS (SG-201C; with 30 mm of the proximal end cutaway), and a CC-4CR-1 curette (all supplied by Olympus Ltd). The curette was inserted into the GS with the tip of the curette exposed outside the GS. The curette and GS were inserted into the bronchoscope. The EWS attached to the curette tip was inserted into the target bronchus and left in position by pulling the curette back through the GS while pushing the EWS with the GS under the bronchoscopic view. The success rate and procedure time were recorded. Results: Bronchial occlusion with an EWS was performed on 143 target bronchi (2 to 9 bronchi/patient). The bronchial occlusion success rate was 98.6%. The median procedure time for bronchial occlusion per EWS on video recordings of the 10 most recent procedures was 110 (range, 40 to 521) seconds. The target bronchial occlusion success rate was 100%. This method enabled easy insertion of the EWS, even in the sharply branching upper lobe bronchus. No complications were observed. Conclusion: Bronchial occlusion using a GS and curette is a rapid and easy technique even in a sharply branching target bronchus.